2009
DOI: 10.1162/jocn.2009.21071
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Effects of Local Context on Target Detection: Evidence from P3b

Abstract: We used the P300 component to investigate how changes in local context influenced the ability to detect target stimuli. Local context was defined as the occurrence of a short predictive series of stimuli before delivery of a target event. EEG was recorded in 12 subjects during auditory and visual sessions. Stimuli were presented in the center of the auditory and visual field and consisted of 15% targets (1000 Hz tone or downward facing triangle) and 85% of equal amounts of three types of standards (1500 Hz, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
67
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 42 publications
(83 citation statements)
references
References 49 publications
15
67
1
Order By: Relevance
“…P3b amplitude increases with increasing stimulus value or relevance to the task (Wilkinson and Morlock 1967;Johnson 1986). In addition, local predictive contextual information has been reported to affect P3b latency (Fogelson et al 2009b;Fogelson and Fernandez-del-Olmo 2011). Past findings show variable effects of exercise and sports on P3b.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…P3b amplitude increases with increasing stimulus value or relevance to the task (Wilkinson and Morlock 1967;Johnson 1986). In addition, local predictive contextual information has been reported to affect P3b latency (Fogelson et al 2009b;Fogelson and Fernandez-del-Olmo 2011). Past findings show variable effects of exercise and sports on P3b.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have shown that predictive local context, defined as the occurrence of a short predictive series of visual stimuli before delivery of a target event, facilitates target detection (Fogelson et al 2009b;Fogelson et al 2010;Fogelson and Fernandez-del-Olmo 2011). These studies identified several neural correlates associated with the facilitation of local contextual processing.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations